On the involvement of the second heart field in congenital heart defects - Guijarro, Clara; Kelly, Robert G. (Comptes Rendus Biologies)
Congenital heart defects (CHD) affect 1 in 100 live births and result from defects in cardiac development. Growth of the early heart tube occurs by the progressive addition of second heart field (SHF) progenitor cells to the cardiac poles. The SHF gives rise to ventricular septal, right ventricular and outflow tract myocardium at the arterial pole, and atrial, including atrial septal myocardium, at the venous pole. SHF deployment creates the template for subsequent cardiac septation and has been implicated in cardiac looping and in orchestrating outflow tract development with neural crest cells. Genetic or environmental perturbation of SHF deployment thus underlies a spectrum of common forms of CHD affecting conotruncal and septal morphogenesis. Here we review the major properties of SHF cells as well as recent insights into the developmental programs that drive normal cardiac progenitor cell addition and the origins of CHD.